2022
DOI: 10.1021/acs.organomet.2c00401
|View full text |Cite
|
Sign up to set email alerts
|

High Activity and Selectivity for Catalytic Alkane–Alkene Transfer (De)hydrogenation by (tBuPPP)Ir and the Importance of Choice of a Sacrificial Hydrogen Acceptor

Abstract: The triphosphorus-coordinating pincer iridium fragment (tBuPPP)Ir was recently reported to be highly active for the catalytic dehydrogenation of n-alkanes. Dehydrogenation is calculated to be highly regioselective for the terminal position of n-alkanes. The extremely high intermolecular selectivity observed in n-alkane/cycloalkane competition experiments supports the prediction of extremely high regioselectivity for dehydrogenation of n-alkanes. The use of sterically unhindered hydrogen acceptors is key to obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Most importantly, the site trans to the central phosphorus is also very crowded; this raises the energy of the square-planar resting state ( tBu PPP)­Ir­(olefin). However, the site cis to the central phosphorus and exo to the bowl-shaped pincer–metal unit is very sterically unhindered , which allows for low-energy transition states (TSs) and intermediates in which the steric demand is shifted to that site. , …”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Most importantly, the site trans to the central phosphorus is also very crowded; this raises the energy of the square-planar resting state ( tBu PPP)­Ir­(olefin). However, the site cis to the central phosphorus and exo to the bowl-shaped pincer–metal unit is very sterically unhindered , which allows for low-energy transition states (TSs) and intermediates in which the steric demand is shifted to that site. , …”
Section: Introductionmentioning
confidence: 71%
“…However, the site cis to the central phosphorus and exo to the bowl-shaped pincer−metal unit is very sterically unhindered, which allows for low-energy transition states (TSs) and intermediates in which the steric demand is shifted to that site. 1,2 Other than iridium, 3,4 the metal that has probably featured most prominently in alkane dehydrogenation is ruthenium. 5−7 Roddick 8,9 and Huang 10,11 have reported examples of high activity with ruthenium complexes of anionic PCP ligands, and we have reported high activity with a ruthenium complex of a neutral PSP ligand.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 , 10 Most recently, the Goldman group showed that (PPP tBu )Ir complexes are remarkably active catalysts for transfer alkane dehydrogenation. 11 , 12 The structurally closest PPP relative comes from the Thomas group ( Figure 1 ), where the central phosphide site is also connected to two nitrogens. 13 , 14 The PPP ligands in the complexes in Figure 1 have been known to form both monomeric complexes with a meridionally binding PPP pincer and dimeric complexes with bridging phosphides, presaging the observations in this work.…”
Section: Introductionmentioning
confidence: 99%
“… Since then, various iridium complexes with other combinations of ligating motifs , and non-iridium transition-metal complexes (Rh, , Ru, Os, and Ti) have been examined, while most of them are less active than the original (PCP)Ir complexes. Recent noteworthy exceptions are the (κ 3 - P , P , P ) pincer iridium complex , and (κ 2 - P , P )­(chloro)­iridium complex, which are effective catalysts for the transfer dehydrogenation of terminal alkanes and 1,1-disubstituted ethanes, respectively.…”
Section: Introductionmentioning
confidence: 99%